2008
DOI: 10.1682/jrrd.2007.09.0145
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Stroke survivors are at high risk for falls in all poststroke stages. Falls may have severe consequences, both physically and psychosocially. Individuals with stroke have an increased risk for hip fractures, and after such a fracture, they less often regain independent mobility. In addition, fear of falling is a common consequence of falls, which may lead to decreased physical activity, social deprivation and, eventually, loss of independence. Important risk factors for falls are balance and gait deficits. Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 530 publications
(105 citation statements)
references
References 141 publications
0
95
0
4
Order By: Relevance
“…In 2008, Weerdesteyn et al reviewed the literature regarding poststroke falls and found a high fall incidence rate after discharge from stroke care: between 1.4 and 5.0 falls each person-year [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, Weerdesteyn et al reviewed the literature regarding poststroke falls and found a high fall incidence rate after discharge from stroke care: between 1.4 and 5.0 falls each person-year [41].…”
Section: Discussionmentioning
confidence: 99%
“…That being said, note that in their recent review of the poststroke falls literature, Weerdesteyn et al stated that some falls after stroke may be inevitable and that fall prevention programming, while effective in improving balance and strength, has not negated poststroke fall risk [41]. History of anxiety was an independent predictor of falls in the acute hospital inpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…1 Comprehensive balance and gait assessment by a physiotherapist is essential to developing treatments aimed at regaining safe independent mobility. Conventional assessment tools used in rehabilitation may identify impairments in balance and gait performance but do not identify the underlying pathophysiological mechanisms responsible for these deficits, which is essential for targeted fall prevention and rehabilitation strategies.…”
Section: Ré Sumémentioning
confidence: 99%
“…Conventional assessment tools used in rehabilitation may identify impairments in balance and gait performance but do not identify the underlying pathophysiological mechanisms responsible for these deficits, which is essential for targeted fall prevention and rehabilitation strategies. 1 Biomechanics technologies, such as force plates and pressure-sensitive mats, have been used in research to provide detailed quantitative information on control of balance and gait but have rarely been incorporated into clinical practice. 2 Understanding the clinician's perceptions and experience of these technologies would be helpful in developing clinical tools and improving the ongoing collaboration between clinicians and researchers required for knowledge translation.…”
Section: Ré Sumémentioning
confidence: 99%
“…This CMS determination conflicts with legislative actions that mandate individuals with disabilities be provided with the necessary supports to live as independently as possible in their communities [1]. Even though increased use of assistive technology devices (ATDs) has been cited as one of the reasons for decreasing disability [3][4] and has positively affected health-related costs by reducing falls and, subsequently, hospital admissions and institutional care [4][5][6][7][8][9][10][11], fewer than 50 percent of older adults with chronic disability and fewer than 25 percent of individuals with recent disabilities received ATDs [12]. Further, only 6 percent of community-dwelling Medicare beneficiaries received any ATDs from Medicare [13].…”
Section: Introductionmentioning
confidence: 99%